Development of an Affordable Internet of Things-Based Remote Humidity and Temperature Monitoring System - Yousfi Jamal; El Malki Mohamed; Bria Abir; Bria Driss (E3S Web of Conferences)
This paper describes the design and arises of a system that directly records sensors involved in temperature and humidity, a microcontroller connected as an operating device primarily concentrated on nominal power energy savings. Results indicate that the system is capable of functioning well on this task, which implies capable generalization to tasks from different domains. At a low cost, and gives it some lightweight portability as well as ease-of-use advantages over the prototype developed in this project. Could eventually become a device that helps in many applications. The demonstrated practicality and accuracy of this prototype position it as a strong contender for future improvements in temperature and humidity measurements.